The Precapillary Segment of the Blood-Brain Barrier and Its Relation to Perivascular Drainage in Alzheimer's Disease and Small Vessel Disease. - Dietmar R. Thal (The Scientific World Journal)
The blood-brain barrier (BBB) is the border between the brain tissue and the blood and consists of a pre- and post-capillary and a capillary segment. At capillaries protein transport is possible via receptor-mediated endocytosis through endothelial cells. At the arteries and veins the BBB is thicker and there is, under physiological conditions, no direct transport from the brain tissue to the blood or vice versa. Here, extracellular fluid is drained into the perivascular space, which is a fluid-filled space between the border of the brain tissue, the glia limitans, and that of the vessel wall, the adventitia as well as along basement membranes within the vessel wall. In the event of degenerative changes in the arterial vessel wall, known as small vessel disease (SVD), leakage of plasma proteins into the vessel wall and into the perivascular space occurs. Thus, the pre-capillary segment of the BBB is altered and drainage of extracellular fluid from the brain tissue competes with the leaking plasma for perivascular drainage. Since the amyloid ß-protein (Aß) is subject of this perivascular drainage and accumulates in the brains of Alzheimer's disease (AD) patients, an alteration of this drainage system in the course of SVD may support the accumulation of Aß within the brain and, in so doing, the development of AD.